Adjuvant nivolumab for stage III/IV melanoma: evaluation of safety outcomes and association with recurrence-free survival - Mandala, Mario; Larkin, James; Ascierto, Paolo Antonio; Del Vecchio, Michele; Gogas, Helen; Cowey, C Lance; Arance, Ana; Dalle, Stéphane; Schenker, Michael; Grob, Jean-Jacques; Chiarion-Sileni, Vanna; Marquez-Rodas, Ivan; et al. (Journal for immunotherapy of cancer, 2021)
BACKGROUND: Several therapeutic options are now available in the adjuvant melanoma setting, mandating an understanding of their benefit‒risk profiles in order to make informed treatment decisions. Herein we characterize adjuvant nivolumab select (immune-related) treatment-related adverse events (TRAEs) and evaluate possible associations between safety and recurrence-free survival (RFS) in the phase III CheckMate 238 trial. METHODS: Patients with resected stage IIIB-C or IV melanoma received nivolumab 3 mg/kg every 2 weeks (n=452) or ipilimumab 10 mg/kg every 3 weeks for four doses and then every 12 weeks (n=453) for up to 1 year or until disease recurrence, unacceptable toxicity, or consent withdrawal. First-occurrence and all-occurrence select TRAEs were analyzed within discrete time intervals: from 0 to 3 months of treatment, from >3-12 months of treatment, and from the last dose (regardless of early or per-protocol treatment discontinuation) to 100 days after the last dose. Possible associations between select TRAEs and RFS were investigated post randomization in 3-month landmark analyses and in Cox model analyses (including a time-varying covariate of select TRAE), within and between treatment groups. RESULTS: From the first nivolumab dose to 100 days after the last dose, first-occurrence select TRAEs were reported in 67.7% (306/452) of patients. First-occurrence select TRAEs were reported most frequently from 0 to 3 months (48.0%), during which the most common were pruritus (15.5%) and diarrhea (15.3%). Most select TRAEs resolved within 6 months. There was no clear association between the occurrence (or not) of select TRAEs and RFS by landmark analysis or by Cox model analysis within treatment arms or comparing nivolumab to the ipilimumab comparator arm. CONCLUSION: Results of this safety analysis of nivolumab in adjuvant melanoma were consistent with its established safety profile. In the discrete time intervals evaluated, most first-occurrence TRAEs occurred early during treatment and resolved. No association between RFS and select TRAEs was evident. TRIAL REGISTRATION NUMBER: NCT02388906.
Keywords: senioři; immunotherapy; melanoma; Immune Checkpoint Inhibitors; Melanoma; výsledek terapie; immunologic; inhibitory kontrolních bodů; programmed cell death 1 receptor; Neoplasm Staging; Nivolumab; Disease-Free Survival; ženské pohlaví; melanom; Humans; staging nádorů; Female; Aged; adjuvants; Treatment Outcome; přežití bez známek nemoci; lidé; nivolumab